2022
DOI: 10.3390/vaccines10121981
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of and Barriers to COVID-19 Vaccine Booster Dose Acceptance in Indonesia

Abstract: Obtaining a booster dose of coronavirus disease 2019 (COVID-19) vaccine is required to maintain the protective level of neutralizing antibodies and therefore herd immunity in the community, and the success of booster dose programs depends on public acceptance. The aim of this study was to determine the acceptance of a booster dose of COVID-19 vaccine and its drivers and barriers in Indonesia. A cross-sectional survey was conducted in the provinces of Indonesia between 1 and 15 August 2022. Individuals who comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In this study, WTP for the booster dose of COVID-19 vaccines in Indonesia tended to be relatively low at 66.2% (1942/2935), yet it is not definite that if this booster dose vaccine is provided free of charge, the public will refuse it, as evidenced by our previous study on the acceptance of booster COVID-19 vaccination in Indonesia [ 31 ]. Variability in WTP for the primary COVID-19 vaccination has been reported in different studies globally [ 17 , 48 , 49 , 50 , 51 , 52 , 53 ]; however, our study can be considered among the first studies to assess WTP for the booster dose of the vaccine.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, WTP for the booster dose of COVID-19 vaccines in Indonesia tended to be relatively low at 66.2% (1942/2935), yet it is not definite that if this booster dose vaccine is provided free of charge, the public will refuse it, as evidenced by our previous study on the acceptance of booster COVID-19 vaccination in Indonesia [ 31 ]. Variability in WTP for the primary COVID-19 vaccination has been reported in different studies globally [ 17 , 48 , 49 , 50 , 51 , 52 , 53 ]; however, our study can be considered among the first studies to assess WTP for the booster dose of the vaccine.…”
Section: Discussionmentioning
confidence: 72%
“…The major finding of the current study was the demonstration of much lower intention to receive the booster doses of COVID-19 vaccination if payment is needed. A recent study among the general public in Indonesia showed that the willingness to receive the booster doses of COVID-19 vaccines, if provided free of charge, was 95% [ 31 ]. The current study with the same target population showed that the need to pay for the vaccine was linked with a discernable decline of willingness to get the booster doses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] Around 71.7% of current study participants believe that a booster dose is required for additional protection against COVID-19, whereas 81.4% of participants in a study from Indonesia believe that booster dose increases immunity, this percentage is quite higher than our study participants. [ 61 ] It is suggesting that knowledge perception and acceptance of the COVID-19 vaccine differs among different populations all over the world. It depends upon their sociodemographic and cultural factors as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, the booster dose coverage was only 24.8%. This lower coverage was despite two studies in Indonesia that found the acceptance of booster dosage was high at 56.3% and 93.9% (Harapan et al, 2022; Wirawan et al, 2022). Understanding the factors contributing to booster shot hesitancy is essential to help policymakers optimize vaccination strategies for COVID-19 control.…”
Section: Introductionmentioning
confidence: 92%
“…However, the booster dose coverage was only 24.8%. This lower coverage was despite two studies in Indonesia that found the acceptance of booster dosage was high at 56.3% and 93.9% (Harapan et al, 2022;Wirawan et al, 2022).…”
Section: Introductionmentioning
confidence: 93%